Reflexe bezvýznamnosti a její možnosti zření (Milan Kundera: »Oslava bezvýznamnosti« – »La fiesta de la insignificancia«) - Urbanová, Svatava (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2016)
The study analyses the most recent novel by Milan Kundera The Festival of Insignificance. The novel explores themes such as existential models and motif variations from previous works by the author including numerous phenomenological filiations. The study theorizes about possible interpretations of the title of the book and the fates of the characters within the life struggles of the given time. It does not exclude the border between life and death. It seeks out answers to questions which emerge and are linked with the position of humans and the roles of one’s own picture of in the eyes of others. The reader becomes witness to both private and public festivals, with both of them, however, bearing the marks of their participants and being connected to the world as a theatrum mundi in which everything is relative.
Keywords: Milan Kundera; Festival of Insignificance; frequent themes; models and motifs; phenomenological filiation